Research and development of innovative underwater cover to eliminate mosquito pupae at Phra Achan Fan Arjaro Hospital in Phanna Nikhom District, Sakon Nakhon Province - Sakhasuvun, Suriya (Disease Control Journal, 2025)
This research aims to study the mortality rates of mosquito pupae, create innovations to eliminate mosquito pupae, and to compare the average mortality rates of pupae. Sample pupae were collected from Village Group Number 8, Ban Khok Chumphon, Panna Subdistrict, Phanna Nikhom District, Sakon Nakhon Province. Experimental research was carried out from October 2024-January 2025 in investigational group and control group, each using 25 pupae and 10 replications tested. All mosquito pupae were classified into Aedes (Aedes aegypti + Aedes albopictus) and Culex pupae. During the study a trial disc, clear acrylic sheet, and product sheet were used as underwater cover inside the containers. The number of pupae deaths was recorded every 6 hours. Results: Mortality rates of Aedes and Culex pupae from a bottle with a lid were 92.00% and 93.20%, respectively. Development results: a trial disc used with a water glass indicated the mortality rates of Aedes and Culex pupae were 98.00% and 95.20%, respectively; while the mortality rates of Aedes and Culex pupae in clear acrylic sheet test unit were 85.60% and 90.80%; and product sheet test units were 85.60% and 90.80%. All experimental units detected the highest mortality rate in the first 6 hours. Results from independent samples t Test on the mean number of deaths of Aedes and Culex pupae in the experimental and control groups of the four pairs compared were significantly different (p<0.05). Aedes pupae: Bottle with/without a lid (MD=22.90; 95%CI=22.52-23.28) Glass with/without trial disc closed under water (MD=24.40; 95%CI=23.98-24.81) tank container with/without clear acrylic sheet closed under water (MD=21.30; 95%CI=20.68-21.92) tank container with/without product sheet closed under water (MD=21.30; 95%CI=20.68-21.92). Culex pupae: Bottle with/without a lid (MD=23.20; 95%CI=22.69-23.71) Glass with/without trial disc closed under water (MD=23.70; 95%CI=22.95-24.46) tank container with/without clear acrylic sheet closed under water (MD=22.60; 95%CI=21.90-23.30) tank container with/without product sheet closed under water (MD= 22.60; 95%CI=21.90-23.30). Innovation from this study are a clear acrylic sheet and product sheet which did not allow mosquito pupae to breathe at the water surface, resulting in its death. Underwater covers made from trial disc, clear acrylic sheet, and product sheet can effectively eliminate mosquito pupae with mortality rate of more than 85.60%. This innovative method maybe applied by a private sector and communities for the prevention and control of mosquito borne diseases.